The estates of the Norman dukes and the Norman kings of England 911-1135 - Dymond, A (2022)
This thesis examines the Norman ducal estates between 911 and 1106 and the English royal estates between 1066 and 1135. The stability and cohesion of these polities, during a period in which socio-political changes led to political decentralization in western Europe, is often explained by the strength of Norman and English institutions. This thesis argues that such institutions were built upon the tangible foundations of wealth and authority provided by the ducal and royal estates. The Introduction sets out the research questions, sketches the source material, and situates the thesis within the existing literature. Chapter 1 discusses the Norman evidence, and the methodological challenges it poses, for reconstructing ducal land. Chapter 2 analyses the early ducal estates between 911 and 1035, demonstrating their geographical distribution within Normandy and the fundamental role they played in the duchy’s formation. Chapter 3 continues the analysis of the ducal estates down to 1106 and discusses how they fit into the duchy’s wider tenurial framework by comparing them with the estates of the Norman aristocracy. Chapter 4 turns to England and explains how Domesday Book is used to identify, reconstruct, and estimate the value of the royal estates under the Confessor and the Conqueror. Chapter 5 demonstrates that royal land doubled in size between 1066 and 1086 but was also conceptually transformed by the conquest. By examining the Conqueror’s antecessores and the narrative accounts, Chapter 5 reconstructs the chronology and process by which this transformation occurred. Chapter 6 looks at the royal demesne under the Conqueror’s sons, who, out of political necessity, granted out considerable portions of Domesday’s terra regis, reducing it to its pre-conquest value. The Conclusion summarizes the principal findings of the thesis, emphasizing the importance of land in underpinning ducal and royal power to shape political structures in Normandy and England. Three appendices, in a separate volume, tabulate the data behind the analysis.